TECHNIQUES FOR FORMATION OF FERROELECTRIC PHOTONIC AND PHONONIC CRYSTALS - V. V. Krutov; A. S. Sigov; A. A. Shchuka (Российский технологический журнал)
Researches in the field of technology of creation of ferroelectric photonic and phononic crystals are analyzed. Features of formation of antiparallel ferroelectric domains are examined by various methods. The special attention is given to the industrially-focused techniques with small duration of a work cycle. Results of the works executed in Moscow Technological University are briefly described. The algorithm for calculating the technological parameters of domain structure formation by the acoustic-interference method is developed. The basic parameters of c-axis-oriented PZT films grown on metallic substrates are estimated. It is shown that the use of the acoustic-interference method allows one to form regular domain structures in PZT films with record-breaking short work cycle duration . The conditions for forming regular domain structures by the double-pulse heterothermal technique are established with regard to new data on heat transfer in films.